Single-Input Regulatory Cascade for in vivo Removal of the Solubility Tag in Fusion Recombinant Proteins Produced by Escherichia coli - Silva, Filipe S. R.; Santos, Sara P. O.; Meyer, Roberto; Alcantara-Neves, Neuza M.; Pinheiro, Carina S.; Pacheco, Luis G. C. (Frontiers in Bioengineering and Biotechnology, 2019)
Solubility tags are commonly fused to target recombinant proteins to enhance their solubility and stability. In general, these protein tags must be removed to avoid misfolding of the partner protein and to allow for downstream applications. Nevertheless, in vitro tag removal increases process complexity and costs. Herein, we describe a synthetic biology-based strategy to permit in vivo removal of a solubility tag (EDA, KDPG aldolase), through co-expression of the fusion recombinant protein (EDA-EGFP) and the tag-cleaving protease (TEVp), in a controlled manner. Basically, the system uses three repressor proteins (LacI, cI434 and TetR) to regulate the expressions of EDA-EGFP and TEVp, in a regulatory cascade that culminates with release of free soluble target protein (EGFP), following a single chemical induction by IPTG. The system worked consistently when all biological parts were cloned in a single plasmid, pSolubility(SOL)A (7.08 Kb, AmpR), and transformed in Escherichia coli Rosetta (DE3) or BL21(DE3) strains. Total soluble recombinant protein yield (EDA-EGFP + free EGFP) was ca. 272.0 ±60.1 µg/mL of culture, following IMAC purification; free EGFP composed great part (average = 46.5%; maximum = 67.3%) of the total purified protein fraction and was easily separated from remaining fusion EDA-EGFP (53 KDa) through filtration using a 50 KDa cutoff centrifugal filter.